The effect of music on arterial blood pressure and anxiety levels in pregnant women hospitalized due to mild preeclampsia: A pilot randomized controlled trial - Yuksekol, Ozlem Dogan; Baser, Muruvvet (Elsevier Science Inc, 2020)
Introduction: Preeclampsia in pregnancy causes fear and anxiety as it may result in maternal mortality. Being an effective relaxation technique, music has been used as an intervention for various health problems, including preeclampsia. This randomized controlled trial aimed to determine whether listening to music could reduce arterial blood pressure and state anxiety in hospitalized pregnant women with mild preeclampsia. Methods: Thirty pregnant women were randomized into intervention group and control group. Data were collected at 3 time points (before lisening to music, 30 min and 60 min after listening to music) both in the morning and evening using the Introductory and Evaluation Form, the Blood Pressure Form, and the State Anxiety Inventory. The arterial blood pressure and state anxiety levels of the pregnant women were measured, and data analysed by chi-square and analysis of variance. Results: Sixty minutes after the intervention, the anxiety score was lower for the intervention group compared with the control group (p < 0.05) after both the morning and evening music listening. Reduction in blood pressure were less consistent probably due to the small sample size. Morning systolicblood pressure was lower in the intervention group than in the control group at 30 and 60 mins after music listening (p < 0.05). There was only evidence for a significant reduction in diastolic blood pressure in the evening 30mins after music listening compared with controls (p < 0.05). Conclusion: Results showed that music had a short term effect on reducing anxiety in preeclamptic pregnant women butthere was only limited evidence in its effect on reducing arterial blood pressure.
Keywords: Anxiety; Arterial blood pressure; Music; Preeclampsia; Randomized controlled trial; Hypertension